Quantification of Lactose in Lactose-Free and Low-Lactose Milk and Milk Products by BIOMILK 300 Lac Biosensor: First Action 2020.09. (14th December 2021) - Garate, Jone; Ortiz de Zarate, Itziar; Gonzalez, Roberto; Jaureguibeitia, Arrate; Salleres, Sandra
Abstract: Background: In 2018, the AOAC Stakeholder Panel on Strategic Food Analytical Methods approved Standard Method Performance Requirement (SMPR ® ) 2018.009, for lactose in low-lactose or lactose-free milk, milk products, and products containing dairy ingredients, establishing the minimum recommended performance characteristics to be addressed during the evaluation of methods. Subsequently, AOAC INTERNATIONAL opened a call for methods under the Official Method of Analysis SM program with the aim of finding a candidate method for confirming compliance with regulatory standards and dispute resolution. Objective: A biosensor-based analytical method, BIOMILK 300 LAC, was developed by BIOLAN Microbiosensores S.L. (www.biolanmb.com ) to rapidly, easily, and accurately quantify lactose in free or low-lactose dairy products. In response to the AOAC call for methods, BIOLAN performed a single laboratory validation of this method against SMPR 2018.009. Several different matrixes were tested, including: milk, sugary plain yogurt, fruit plain yogurt, flavored liquid yogurt, Greek yogurt, cream, soft cheese, infant formula, café latte, chocolate milk, and high-protein milk shake. Evaluated method parameters included: linearity, selectivity, matrix effect, recovery, accuracy, repeatability, intermediate reproducibility, robustness, reagent lot-to-lot consistency, and stability. Methods: The method is based on the use of the Biotest gold electrode together with the BIOMILK 300 biosensor reader, for the quantification of residual levels of lactose in dairy samples via an enzymatic recognition/electrochemical transduction system. Results: Assay linearity, applicability to different matrixes, recovery, and precision demonstrated that the method is fit for purpose. The method proved to be robust, consistent, and stable, under conditions detailed in the Instructions For Use guide. Conclusion: The overall results were within requirements stated by SMPR 2018.009 for low-lactose and lactose-free milk, milk products and products containing dairy ingredients. Highlights: The BIOMILK 300 LAC method enables the quantification of reduced levels of lactose in less than 5 min, without the requirement for expert technicians, toxic solvents or intricate procedures, maintaining a high degree of precision and accuracy in the results. BIOMILK 300 LAC was adopted as a First Action Official Method SM by the Expert Review Panel of Low-lactose Methods in April 2020 after rigorous review.